The Use of Cultural Transposition for Rendering Culture-Specific Items in English-to-Indonesian Translation of Brown’s Inferno - Alimul Khakim, Muhammad; Anggani Linggar Bharati, Dwi; Mujiyanto, Januarius (English Education Journal, 2019)
Translation always involves the transfer of culture between languages. Culture-specific items (CSIs) are objects of translation that often make translator find difficulty due to their peculiarity that root in source language (SL) culture. This requires the translator to consider both the SL culture and target language (TL) culture. Cultural transposition that consists of exoticism, cultural borrowing, calque, communicative translation, and cultural transplantation are translation procedures that concern with the transfer of culture between languages. This research is aimed to analyze the implementation of these procedures in rendering CSI from English to Indonesian. This study employed a descriptive qualitative research approach. The interpretation of the data is described in depth explanation. The object of this study is CSI extracted from Brown’s Inferno novel. The results of this study show that almost all of the cultural transposition procedures are implemented in rendering CSI in all categories. Results also show how these procedures are implemented in practices. Exoticism is implemented on items that are very peculiar to SL or items that derive from language that is not popular in TL. There are also a large number of CSI in the form of names that requires the translator to transfer the item without modification. Cultural borrowing procedure is implemented in on items that are strange but derive from language that is popular in TL or items in which TL culture have owned their general kind. This is done by phonological adjustment and specification. Calque is implemented on CSI in which their elements can be translated to TL. Results also show CSIs in the category of names are rendered using calque. Meanwhile, communicative translation and cultural transposition, from the result, only occur in CSI in the form of common expressions. Communicative translation occurs in rendering CSI that requires an explanation for its peculiarity. This is done by making a simple description that explains the CSI. Cultural transplantation is implemented in CSI that is developed differently in TL such as measurement/scales. This is done by rendering items with others that are similar or by converting that scales roughly. As the conclusion, there is a tendency that CSIs are rendered with SL biases procedures that bring TL readers to SL cultures.